Influência do uso de máscara de proteção facial sobre o desempenho físico, cognitivo e no equilíbrio corporal dinâmico em ambiente quente e temperado - Gabriel Resende Quinan (2014)
The work environment in the construction industry provides high physical demand for workers. In an attempt to prevent accidents in the workplace, it is necessary and often required, the use of personal protective equipment (PPE). The use of PPE may impose additional physiological and psychological stress for workers which added to the heat stress and possible dehydration can negatively influence physical performance, cognitive function and balance of the body, affecting the performance of the task, and possibly increasing the risk of accidents in the workplace. Therefore, the aim of this work was to verify the influence of the use of a protective mask against toxic gases in the physical performance, cognitive performance and balance in both environments (hot and temperate). Four experimental situations that had at last 90 minutes (3 sets of 20 minutes walk and 10 minutes from Repetitive Box Lifting modified) were performed simulating a work routine. The situations defined were performed without use face mask protection in temperate environment (SMT), using the mask in temperate environment (CMT), without use of the mask in a hot environment (SMQ), and using the mask in a hot environment (CMC). The temperate environment showed 24 C and 73% RH and warm environment 36 C and 75% RH. Physical performance, cognitive performance and balance were evaluated. No significant differences were found in any of the variables of physical and cognitive performance and balance, however significant differences were observed in perceived exertion during the 90min. Thus, we conclude that the use of facial protection mask does not affect physical performance, cognitive function and balance in a work simulation lasting 90 minutes.